Students' Perception of The Use of Spotify in Learning English - Yaneva, M. Farhan Alfaruqqi; Viana, Okta; Akbar , Gian Fadillah (IJLHE: International Journal of Language, Humanities, and Education, 2018)
People can now bring their music and podcast with them because of the existence of smartphones, which can hold a large number of tunes. New ways to listen to music every day when freemium music-streaming apps like Spotify arise. Spotify is one of the world's most popular music streaming services, having been created in 2008. It is a multimedia program that may also be used to teach listening skills. This research aimed to identify if Spotify can help students improve their English listening skills. The researchers distribute a questionnaire to students to see how Spotify affects their English listening skills. This research uses using sampling technique: The purposive Sampling Technique. The results revealed that students could enhance their listening skills by utilizing Spotify in an English listening class. This research also revealed that listening to Spotify daily can help students improve their English listening skills and succeed in various English courses. According to the study, Spotify can assist students in improving their English listening skills. More studies could be done to investigate multimedia applications to help students improve their listening skills.